Selective synthesis of α-organylthio esters and α-organylthio ketones from β-keto esters and sodium S-organyl sulfurothioates under basic conditions - Kazmierczak, Jean C.; Cargnelutti, Roberta; Barcellos, Thiago; Silveira, Claudio C.; Schumacher, Ricardo F. (Beilstein Journal of Organic Chemistry, 2021)
We described herein a selective method to prepare α-organylthio esters and α-organylthio ketones by the reaction of β-keto esters with sodium S-benzyl sulfurothioate or sodium S-alkyl sulfurothioate (Bunte salts) under basic conditions in toluene as the solvent at 100 °C. When 4 equivalents of a base were used, a series of differently substituted α-thio esters were obtained with up to 90% yield. On the other hand, employing 2 equivalents of a base, α-thio ketones were achieved after 18 h under air. Furthermore, after a shorter reaction time, the isolation of keto–enol tautomers was possible, revealing them as significant intermediates for the mechanism elucidation.
Keywords: α-alkylthio esters; α-alkylthio ketones; Bunte salts; C–C bond cleavage; β-keto esters